THEORETICAL AND PRACTICAL INTEGRATION OF THE USE OF GAMES IN VOCABULARY TEACHING - Dilnoza Mamanova Abdurashid qizi,; Nigina Amirova O‘ktam qizi,; Farida Abdumannonova Komiljon qizi, (TADQIQOTLAR, 2025)
Annotation:  This  article  thoroughly  analyzes  the  theoretical  and  practical foundations  of  using  game  technologies  in  the  vocabulary  teaching  process.  Game methods  are  highlighted  in  connection  with  the  psychology  of  language  learning, cognitive  processes,  motivation,  memorization  mechanisms,  and  their  role  in  the development of communicative competence. During the study, the effectiveness of vocabulary  acquisition  through  games,  the  advantages  of  digital  platforms,  role-playing games, problem-situational games, strategic games, and language games added to the lesson process are demonstrated with practical examples. The article analyzes, based on statistical data, the influence of game methods on the quality of education, students'  active  participation,  the  level  of  assimilation,  motivation  indicators,  and changes  in  the  teacher's  pedagogical  skills.  The  conclusion  contains  proposals  for future research.